Upaya Meningkatkan Prestasi Belajar Siswa Pada Pelajaran Pai Pokok Bahasan Aku Anak Shalih Melalui Metode Pembelajaran Tanya Jawab : (Penelitian Tindakan Kelas Di Kelas IV SDN Sukaurip 2 Balongan Indramayu) - Muasromatul Azizah (Khulasah : Islamic Studies Journal, 2020)
Based on empirical observations in class IV of SD Negeri Sukaurip 2 Balongan Indramayu, the author observed that the implementation of learning methods that have been applied so far tend to be passive, so that students are less interested in the methods applied by PAI subject teachers. As an implication of the student's lack of interest, student learning outcomes tend to not meet the KKM (Minimum Completeness Criteria). Therefore, the author is interested in applying the question and answer learning method to PAI subjects in class IV of Sukaurip 2 Balongan Indramayu Elementary School, with the hope that student activity in taking these subjects will be good and ultimately student learning outcomes will improve. The method used in this research is classroom action research. The term classroom action research is used to emphasize the classroom as the setting of the research. The subjects in this research were a teacher (writer) and Class IV students at Sukaurip 2 Balongan Indramayu Elementary School, totaling 27 students. In practice, the cycles applied are three cycles, namely Cycle I, Cycle II, Cycle III. In this research, the research instruments used were as follows: (1) Observations regarding the implementation of the question and answer learning method in PAI subjects regarding the material I Am a Pious Child in Class IV of Sukaurip 2 Balongan Indramayu Elementary School. (2) Interviews with students regarding the question and answer learning method applied by PAI subject teachers on the subject of Solid and Liquid Objects, and Changes in Their Forms. and (3) Value of student learning outcomes in PAI subjects on the subject of Solid and Liquid Objects and Changes in Their Forms, taken from Cycle I, Cycle II, and Cycle III. Based on research that has been carried out, it can be concluded that by learning using the question and answer learning method, student learning outcomes have improved. In the pre-cycle the average learning outcome was 51.48, and in the first cycle the average learning outcome was 61.48, and in the second cycle the average learning outcome was 69.25. The average value of learning outcomes in pre-cycle, cycle I and cycle II still does not meet the KKM (Minimum Completeness Criteria). Meanwhile, in cycle III, the average learning outcome was 77.03.